Enhancing Electoral Geography: Utilizing Geospatial Technologies to Ana-lyze Recent Hispanic Voting Patterns in the United States - Weichelt, Ryan (Geopolítica(s). Revista de estudios sobre espacio y poder, 2018)
Early electoral research analyzed elections as whole areal ecological units such as individual states to examine how people voted. However, in the 1920s, political scientists began to place a strong emphasis on individual voter behavior, becoming increasingly reliant on survey data. Electoral geographers who utilized surveys were always troubled with this method due to the difficultly of connecting geographic voting patterns to individual respondents. The rise of positivism in the 1960s, inspired electoral geographers to re-center their focus on the voting behavior of large groups in the aggregate, not the individual. While qualitative methods still have an important role to play in electoral inquiry, the growth of geospatial technologies and increased interests in electoral cartography can yield important insights and should be utilized more in the study of elections. This paper will highlight a variety of spatial analysis techniques (i.e. cartographic methods, spatial statistics, and spatial autocorrelation) focusing on the recent electoral patterns of Hispanic voters in the United States. By providing a robust discussion of geospatial analysis methods, this paper can provide new avenues of discussion regarding geography’s role in the study elections.
Keywords: electoral geography; Hispanic voting; USA; spatial analysis; geospatial technologies